ANALISIS META-SINTESIS DAMPAK ARTIFICIAL INTELEGENCE TERHADAP PERFORMA AKADEMIK DI ERA DIGITAL - Fahlapi, Fasha; Syafitri, Khairunnisa; Ibrahim, Surya Rizky Maulana; Ilham, Farizi (JUTECH : Journal Education and Technology, 2024)
Artificial Intelligence (AI) offers innovative solutions to improve the quality of teaching and learning, providing significant benefits to students and educators. This research aims to analyse the potential and challenges of implementing generative AI in education in the digital era using a qualitative meta-synthesis approach. Data from previous literature shows that generative AI can increase personalisation of learning by 30%, reduce administrative burden by 40%, and improve academic outcomes by 20%. However, challenges such as data privacy risks, technology dependency, and digital access gaps remain major obstacles. The results of this study recommend the integration of generative AI into education through classroom learning of AI use, discussions between educators and students, and limits on technology use. At the curriculum and policy level, adaptive and inclusive strategies are needed to adjust to technological developments. In addition, this research proposes government policies that support the adoption of AI in education and provides practical guidelines for responsible implementation. Further research is expected to empirically analyse the adoption process and measure the readiness and perception of stakeholders in Indonesia. With the right approach, generative AI can become a valuable learning tool, sustainably transforming modern education.